Development Analysis and Perspective on LTE Current Status - Wenyu Li; Lina Song; Xiumiao He (Dianxin kexue)
Long term evolution technology（LTE）is a new generation of wireless communications technology. LTE has experienced a rapid development process since 2010. And by the end of 2013, 260 LTE networks has been launched. Chinese government also issued TD-LTE licenses on Dec. 2013. It was specified that LTE was the hot technology based on current wireless markets and technology development. Current LTE development status and challenge it faced were analyzed. Also the positive impaction to TD-LTE globalization brought by Chinese TD-LTE license issuing was analyzed. Based on the analysis, some perspects on LTE development in future were conducted, especially in 2014.